O CMS e-Lab e o ensino de física de partículas na educação básica - Alves , Marcos Fabrício Lopes (2018)
Electronic Laboratories (E-Labs) are online resources designed for high school students to use research data obtained from authentic scientific experiments in individual or group investigations. It aims to bring topics of particle physics, matter and dark energy, gravitational waves, into high school, stimulating students through involvement in research scripts using data produced in large research centers in these areas. The CMS e-Lab provides collision product data between accelerated protons in the LHC (Large Hadron Collider) and detected by the CMS (Compact Muon Solenoid) experiment. It provides students with an environment in which they can carry out individual or group investigations using available data, an opportunity to see how the great scientific discoveries are made, and to make their own "discoveries" and publish them, informing them of the production process and dissemination of contemporary science. In this opportunity to "put their hand to the mass", basic knowledge of Elementary Particle Physics (EPP) is developed, in addition to students obtaining a practical view of such contents, partially bypassing the lack of equipment and experiments in this area, in general expensive and inaccessible to regular educational institutions. The CMS e-Lab, as a resource for the teaching of EPP, lends itself to use as an additional teaching material, in addition to allowing different teaching strategies. The present work aims at the feasibility analysis of the use of the CMS e-Lab as a resource for the teaching of Elementary Particle Physics.